Political culture and entrepreneurial activity as prerequisites for positive development in Bulgaria - Pastarmadzhieva, Daniela; Angelova, Mina (Leadership, Society, Strategic Visions, 2021)
Thirty years ago, Bulgaria made a shift towards democratic development, but the social environment has the potential to strengthen or undermine the selected direction. The aim of the current work is to identify the state of Bulgarian political culture and entrepreneurial activity and make a forecast about their future development. The object of the study is Bulgaria since 1989. The focus are a selection of indicators, regarding the political culture and entrepreneurial activity. In order to achieve our goal we make review of the studies, regarding the topic and use quantitative data in order to evaluate the political culture and entrepreneurial activity. Among the sources are European values study, World values survey, Eurostat and Global Entrepreneurship Index.